Exploring the Teachers’ Understanding of the Role and Functionality of School-Based Support Teams - Netshipale, Adziliwi Martha; Tlale, Lloyd Daniel Nkoli; Phala, Thembi Anastacia Lucky (Studies in Learning and Teaching, 2025)
Teachers’ understanding of the role and functionality of School-Based Support Teams is critical in executing the responsibilities of teaching, learning and provision of additional support to their learners. The study explored participants’ views, experiences, knowledge and practices on their understanding of the role and functionality of school-based support in education. Qualitative approach, interpretivism paradigm, and instrumental case study design were adopted. Purposeful sampling method was used to select 35 participants from five rural secondary schools (ten members of school governing bodies, five principals, fifteen teachers who were members of school-based support teams and five district-based support team members). Questionnaires, field notes, focus groups and individual interviews were used to collect data. The results showed that teachers had a clear understanding of the role and functionality of school-based support teams. However, due to time constraints, they prioritize the completion of a syllabus over engaging in support teams. The study's recommendations included the provision of additional human resources in schools to assist teachers.